Usaha Produk Besek dalam Meningkatkan Ekonomi Keluarga berdasarkan Ekonomi Islam : Studi Kasus di Desa Ciderum Kampung Batukembar - Jubaedi, Ahmad; Asri, Kholifatul Husna (ALIF: Sharia Economics Journal, 2024)
Family economy is an important foundation in community life, including in Ciderum Village, Batukembar Village. This village relies mainly on agriculture and local crafts, with the majority of the population involved in these businesses. Unfortunately, the level of economic welfare of families in Ciderum Village is still below expectations, with many residents struggling to meet basic needs such as food, education, and health. In addition, the majority of the population of Ciderum Village are Muslims who practice the principles of Islamic economics, which emphasize justice, togetherness, and blessings in economic transactions. However, the application of these values ??has not been seen in daily economic activities in this village. In this context, besek products are a great opportunity to improve the family economy in Ciderum Village. Besek is a traditional craft that has existed for a long time in this village. By utilizing the potential of besek and implementing Islamic economics, we can improve the family economy in Ciderum Village. This study aims to investigate efforts to develop a besek product business based on Islamic economic principles in this village. The aim is to identify opportunities and challenges in implementing Islamic economics in the besek product business and to analyze its impact on the family economy in the village. This study uses a qualitative research method whose object of research is bamboo or besek craft business, including descriptive qualitative research. It is hoped that this study will provide practical guidance for the people of Ciderum Village in developing sustainable besek product businesses that are in accordance with Islamic economic values. In addition, the results of this study can also contribute to the development of a sustainable economy in rural areas, especially in Ciderum Village, and provide insight into the potential of Islamic economics in improving family welfare.